Harmonisasi SAK dan Aturan Pajak: Mungkinkah? - Sukendar, Heri Sukendar (Bina Nusantara University, 2014)
This paper is intended to illustrate the fact that the case today, especially in Indonesias commitment to convergency of IFRS, where the decision was certainly not out of global importance that in order to improve the information from the financial statements of companies in Indonesia. In addition, the IFRS Convergence is one of the Indonesian government agreements as a member of the G20 forum, the results of the meeting of G20 leaders in Washington DC forum, 15 November 2008. On the other hand, the tax rules that apply are still using the old accounting standards and do not follow the development of increasingly different. Previous differences between GAAP and tax rules are limited to the